The physics companion - Fischer-Cripps, Anthony C. (CRC Press, 2015)
Updated and expanded with new topics, The Physics Companion, 2nd Edition offers a unique and educational approach to learning physics at a level suitable for first-year science students. This new edition expands the presentation to include senior topics, such as statistical mechanics, quantum physics, and nuclear physics.